The quest begins Seekers - Hunter, Erin. (New York : HarperCollins, 2008)
Three young bears of different species--one black, one polar, and one grizzly--travel on a perilous quest to the Northern Lights, escorting a shape-shifting grizzly cub whose destiny will affect them all.
Keywords: Bears -- Juvenile fiction; Bears -- Fiction; Fantasy; Fantasy fiction